FSMP-15. EVALUATING THE ROLE OF LONG-CHAIN FATTY ACID METABOLISM IN PROMOTING GLIOBLASTOMA GROWTH. (25th March 2021) - Ravi, Divya; del Genio, Carmen; Ghiasuddin, Haider; Gaur, Arti
Abstract: Glioblastomas (GBM) or Stage IV gliomas, are the most aggressive of primary brain tumors and are associated with high mortality and morbidity. Patients diagnosed with this lethal cancer have a dismal survival rate of 14 months and a 5-year survival rate of 5.6% despite a multimodal therapeutic approach, including surgery, radiation therapy, and chemotherapy. Aberrant lipid metabolism, particularly abnormally active de novo fatty acid synthesis, is recognized to have a key role in tumor progression and chemoresistance in cancers. Previous studies have reported a high expression of fatty acid synthase (FASN) in patient tumors, leading to multiple investigations of FASN inhibition as a treatment strategy. However, none of these have developed as efficacious therapies. Furthermore, when we profiled FASN expression using The Cancer Genome Atlas (TCGA) we determined that high FASN expression in GBM patients did not confer a worse prognosis (HR: 1.06; p-value: 0.51) and was not overexpressed in GBM tumors compared to normal brain. Therefore, we need to reexamine the role of exogenous fatty acid uptake over de novo fatty acid synthesis as a potential mechanism for tumor progression. Our study aims to measure and compare fatty acid oxidation (FAO) of endogenous and exogenous fatty acids between GBM patients and healthy controls. Using TCGA, we have identified the overexpression of multiple enzymes involved in mediating the transfer and activation of long-chain fatty acids (LCFA) in GBM tumors compared to normal brain tissue. We are currently conducting metabolic flux studies to (1) assess the biokinetics of LCFA degradation and (2) establish exogenous versus endogenous LCFA preferences between patient-derived primary GBM cells and healthy glial and immune cells during steady state and glucose-deprivation.